Kemampuan Kerja Aparat Kecamatan Dalam Memberikan Pelayanan Administrasi Akte Jual Beli Tanah Kepada Masyarakat Di Kecamatan Tikala Kota - Gosal, Macky F.E; Kimbal, Marthen; Rumawas, Wehelmina (JURNAL ILMIAH SOCIETY, 2016)
The purpose of this study was to assess the ability of the District Officers Working in Providing Administrative Services Purchase Deed Land to the People in District Tikala Manado City. The research methodology used is qualitative research. Informants in this study were taken from the public, community leaders and governments in Sub Tikala by 10 informants The results showed that in providing services deed of sale of land generally apparatus own technical abilities quite like the ability to use knowledge concerning administrative services deed of sale and purchase of land in terms of the process until the rules that must be met, with the knowledge it easier for employees to be able to work in providing administrative services deed of sale and purchase of land to the community, there is a portion of the apparatus that do not have adequate knowledge in the performance of its duties regarding the administrative services deed of sale and purchase of land, but coworkers are always trying to provide help, so that administrative services to the community is not disturbed. For social skills are good enough proven apparatus of the apparatus has the capability of other people's motives as well as collaborating with colleagues in performing the duties of administrative services deed of sale and purchase of land to the public. Conceptual abilities are good enough apparatus wherein the apparatus is enough to have the ability to understand the complexity of the organization as a whole. Keywords : performance, administration